PREVALENSI DIABETES MELLITUS TIPE 2 PADA ANAK DAN REMAJA (STUDI LITERATUR) - Gangga Mahatma; Wisda Widiastuti; Riki Nova; Anita Darmayanti; Abdullah, Dessy (Nusantara Hasana Journal, 2024)
Type 2 Diabetes Mellitus is a long-term medical illness marked by high blood sugar levels caused by the body's ineffective use of insulin. The increasing frequency of this problem in not just adults but also in children and adolescents is causing alarm. An overview of Type 2 Diabetes Mellitus detection, diagnosis, treatment, and risk factors is intended to be provided by this review of the literature. The review's research sources come from a number of respected scientific periodicals.The information included in this literature review comes from a variety of scientific papers that have been published in the recent five to ten years in both domestic and foreign journals. Using the following keywords, a comprehensive search of several databases, including PubMed, the Cochrane Library, and Google Scholar, produced these articles: "type 2 diabetes mellitus," "children," "adolescents," "epidemiology," and "risk." The findings indicate that Type 2 Diabetes Mellitus is becoming more common in children and teenagers, particularly in developing nations. Unhealthy lifestyle choices such an unbalanced diet and inactivity are associated with this trend (Rahmayunita et al., 2023). Significant concern also surrounds the long-term consequences of Type 2 Diabetes Mellitus in children and adolescents, which include retinopathy, nephropathy, cardiovascular disease, and neuropathy (Rahmayunita et al., 2023; Wijayanti et al., 2020; Kusumastuti et al., 2023; Andriyani et al., 2022).Medical teams, parents, and the patients themselves must work together to manage Type 2 Diabetes Mellitus in children and adolescents. For this condition to be prevented and controlled from progressing, early detection, suitable treatment, and lifestyle modifications toward healthy habits are essential.